Effect Of Various Flowsheets On Efficiency Of Phosphate Recovery At Peace Valley, Florida - I. Milton LeBaron (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1946)
OPERATION of the phosphate flotation plant at the Peace Valley mine of the International Minerals and Chemical Corporation, Florida, began in the summer of [ ] 1942. Since that time several changes have been made in the flowsheet, with resultant increases in metallurgical results. Three flowsheets, together with the comparative plant results, are given in this paper, together with a discussion of the desliming circuit used for preliminary washing of the flotation feed. FIRST FLOWSHEET CHANGES Fig. I lists the essential units in the original flowsheet at the Peace Valley plant. The figures for tonnage and grade are average for a period of two months. Mineral Separation Airflow cells are used for both the fatty acid and the amine float. Three immediate difficulties presented themselves in the use of this flow sheet: I. Floating a maximum amount of phosphate in the rougher section to give good recovery sent a low-grade concentrate to the silica float, resulting in high costs for amine reagent in that section.